Synthesis, characterization and biocompatibility of guar gum-benzoic acid - Le Trung-Anh; Guo Yong; Zhou Jun-Nian; Yan Jiaqi; Zhang Hongbo; Huynh Tan-Phat (ELSEVIER, 2025)
A novel chemical functionalization of guar gum (GG) by benzoic acid (BA) via nucleophilic substitution reaction in aqueous solution has been reported. BA moieties are chosen due to coordination chemistry of carboxylic acid moieties, hydrophobicity and intermolecular interaction of aromatic rings. The presence of conjugated BA on guar gum-benzoic acid (GG-BA) with grafting density of 5.5% is confirmed by 1H NMR. Amorphous GG-BA with irregular morphology has been studied by UV-Vis, FTIR, XRD, SEM, TEM, TGA, computational chemistry and contact angle measurement. GG-BA in a concentration range from 0 to 4000 mu g mL-1 has good biocompatibility to mouse embryonic fibroblasts (MEF), human mammary epithelial cells (MCF-10A) after 48 and 72 h of treatment using WST-1 assay. GG-BA shows great potential for the development of biomaterials such as bioadhesives, hydrogels, and coacervates.